2019
DOI: 10.1002/eat.23054
|View full text |Cite
|
Sign up to set email alerts
|

Test of the modified dual pathway model of eating disorders in individuals with type 1 diabetes

Abstract: Objective: Adolescents and young adults with type 1 diabetes (T1D) demonstrate high rates of disordered eating behaviors (DEBs) and may experience physiological and psychological vulnerabilities not currently included in established risk models of DEBs. This study examined associations among constructs included in the recently proposed T1D-specific modified dual pathway model and examined age as a moderator of these associations.Method: Participants included adolescents (n = 307; age M = 15.71, SD = 1.33), you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
0
17
0
4
Order By: Relevance
“…Recent research has shown empirical support in youth and young adults with type 1 diabetes for the link between disordered eating and certain aspects of this model (e.g. hunger/satiety disruption, dietary regimen, negative affect) . In parallel to development of the modified dual pathway model, Treasure et al .…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown empirical support in youth and young adults with type 1 diabetes for the link between disordered eating and certain aspects of this model (e.g. hunger/satiety disruption, dietary regimen, negative affect) . In parallel to development of the modified dual pathway model, Treasure et al .…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…to be a salient feature in both restrictive and disinhibited subtypes, as it may be characterized as a control-seeking behaviour (when combined with dietary restraint or perfectionistic attitudes) or a compensatory purging behaviour (e.g. when engaged in after an episode of binge eating) [14,15]. Profiles or subtypes of disordered eating in type 1 diabetes may also differ with respect to their trajectories, with some investigations noting variability in the persistence of symptoms over time [5,6,16].…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…Aufgrund der bedeutsamen somatischen Konsequenzen bereits sub- klinisch gestörten Essverhaltens bei Menschen mit Diabetes ist eine frühzeitige Identifizierung der Betroffenen in der Praxis elementar. Regelmäßiges Screening in internistischen Diabetes-Schwerpunktpraxen im Kontext der Diabetesbehandlung erscheint aufgrund der hohen Prävalenz gestörten Essverhaltens in dieser Patientengruppe empfehlenswert, um Betroffene frühzeitig zu identifizieren, zu informieren und bei Bedarf eine Behandlung in die Wege zu leiten [30]. Zudem fanden sich bei den Teilnehmenden mit Auffälligkeiten im Essverhalten signifikant häufiger u. a. schwere Ketoazidosen und Krankenhausaufenthalte im letzten Jahr.…”
Section: Diskussionunclassified
“…In der vorliegenden Studie erwiesen sich u. a. das HbA1c, der BMI, das Geschlecht und diabetesbezogene Belastungen (PAID-5) als bedeutsame Prädiktoren für das Ausmaß gestörten Essverhaltens. Auch Rancourt und Kollegen fanden, dass diabetesspezifische Belastungen mit einem höheren Ausmaß an gestörtem Essverhalten einhergingen [30]. Bei der Diabetesdauer zeigte sich ein kleiner Effekt für eine kürzere Diabetesdauer als Prädiktor für gestörtes Essverhalten.…”
Section: Diskussionunclassified